If it's not what You are looking for type in the equation solver your own equation and let us solve it.
b+42=3b
We move all terms to the left:
b+42-(3b)=0
We add all the numbers together, and all the variables
-2b+42=0
We move all terms containing b to the left, all other terms to the right
-2b=-42
b=-42/-2
b=+21
| 3x-8+4x=2x+18-6x | | 3x^2+5x+56=0 | | 9(f-94)=45 | | J=5x-2 | | x+5(6-8)-4=4+5x-2 | | 193=8b^2-7 | | 9(f−94)=45 | | 2/9q=-5/8 | | n^2+18n+61=-4 | | n÷3-4=20 | | 2(y-56)=60 | | 3(-x)-2(-x)-(-4)=(-x)-x+1 | | 2(y−56)=60 | | x^2−2x−24=0 | | 96=6(n+2) | | 3-4r=-25 | | x^2−2^x−24=0 | | 5r^=80 | | 48=4(h+72) | | h2-3h=8 | | 12.3=41x | | -15-y=31 | | 2p-3.7=2.3 | | 5/6x+2/3=1/2x-10/3 | | 4(u+100)=0 | | 44=9n+8 | | -5(m+32)=-75 | | 6(u+6)=90 | | h/3+8=15 | | 3.6/x=-5 | | 16-y=25 | | -2=4+n/9 |